Memahami Interaksi School Well Being dan Teori Motivasi Vroom terhadap Keterlibatan Siswa: Studi Literatur pada Era Kurikulum Merdeka - Putri Nurul Hanifah; Sabrina Davindri Tri Anugrah S (P3I UMSurabaya, 2024)
Education is the main foundation for the nation's progress, students are trained and developed through the availability of schools, and the government is also trying to develop and implement an independent curriculum. However, this will become a problem if schools cannot provide good facilities to support students' basic needs, negatively impacting students with decreased learning motivation and student engagement in school. Therefore, this study examines the relationship between school well-being and Vroom's theory of motivation in the context of student engagement in the era of implementing the Merdeka Curriculum. Using a qualitative approach based on a literature study, this research aims to understand how school well-being and motivational expectations based on Vroom's theory interact in shaping students' active engagement in the learning process.